AI and its Effects on Financial Markets - Palivos, Stephanos (Open Schools Journal for Open Science, 2024)
Artificial Intelligence (AI) is revolutionizing the financial sector by transforming various aspects such as algorithmic trading, personalized financial advising, fraud detection, and investment analysis. This paper explores how AI technologies are integrated into financial markets, enhancing efficiency, accuracy, and security. The discussion covers the nature of AI in financial markets, its benefits, challenges, and the future outlook.